2019
DOI: 10.7819/rbgn.v21i5.4030
|View full text |Cite
|
Sign up to set email alerts
|

A Chain Multiple Mediation Model Linking Strategic, Management, and Technological Innovations to Firm Competitiveness

Abstract: Purpose -This study attempts to build an integrated framework to discuss the influence of three types of innovations, i.e. strategic, management, and technological innovations, on firm competitiveness.Design/methodology/approach -Paired survey responses are collected from 303 firms located in China. A confirmatory factor analysis is implemented with SPSS AMOS software to check the reliability and validity of all measures through structural equation modeling. Four hypotheses are empirically examined with SPSS P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Product innovation has attracted a large amount of attention in the literature (Carranza, 2010); (Corsino & Gabriele, 2010); (Fontana & Nesta, 2009); (Kusiak, 2009), and research have shown its direct effect on company performance. Research carried out by Han and Gao (2019), with empirical tests from survey data collected from 303 companies in China, supported a positive relationship between innovation strategies with company performance. It was because, specifically, the innovation strategy could improve competitiveness associated with company performance.…”
Section: H1mentioning
confidence: 91%
“…Product innovation has attracted a large amount of attention in the literature (Carranza, 2010); (Corsino & Gabriele, 2010); (Fontana & Nesta, 2009); (Kusiak, 2009), and research have shown its direct effect on company performance. Research carried out by Han and Gao (2019), with empirical tests from survey data collected from 303 companies in China, supported a positive relationship between innovation strategies with company performance. It was because, specifically, the innovation strategy could improve competitiveness associated with company performance.…”
Section: H1mentioning
confidence: 91%
“…Strategic flexibility (10 items) was operationalized using the approach of Li et al [75]. Strategic innovation (4 items) was operationalized with reference to Han and Gao [69]. Environmental uncertainty (9 items) was measured based on Chen et al [76].…”
Section: Methodsmentioning
confidence: 99%
“…Some existing literature has identified the positive relationship between strategic flexibility and strategic innovation. Utilizing survey data from 303 Chinese manufacturing, Han and Gao [69] verified that strategic flexibility improves management innovation through the mediator of strategic innovation. Han and Gao [69] also proved that employee orientation positively influences strategic flexibility and strategic innovation orderly, which, in turn, improves original innovation.…”
Section: Strategic Flexibility and Strategic Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…After passing the joint significance and robustness tests, we further test the hypotheses using bootstrapping and Monte Carlo methods (Kenny et al, 2016). We set the sample size to 5000 (Han & Gao, 2019). Table 7 shows the total, direct and indirect effects and effect size.…”
Section: Mediation Tests Based On Bootstrappingmentioning
confidence: 99%